Monogenoideos branquiales en Pterophyllum scalare (Schultze ,1823) y Biotodoma cupido (Heckel, 1840) (perciformes: cichlidae) provenientes del río Itaya, Iquitos, Perú - Vásquez Arimuya, Mariana (2023)
The present study was carried out in the Laboratory of Parasitology and Aquaculture Health of the Peruvian Amazon Research Institute (IIAP), in a period of six months, from May 28 to October 20; The purpose of this research was to make the taxonomic identification of species of parasitic monogenoids of the gills of Pterophyllum scalare "angelfish"; and Cupid Biotodoma “pretty face”. The fish were acquired through fishermen from the Itaya River, specifically from the community of San Andrés, a place that is located in the District of Belén, Province of Maynas, department of Loreto, Peru. Those who were entrusted with the fishing for their subsequent sale of the captured specimens. 30 specimens of Pterophyllum scalare and 30 of Biotodoma cupido were acquired, making a total of 60 individuals. The fish were transferred in plastic bags to the Aquaculture Parasitology and Health Laboratory (IIAP). The samples were subsequently analyzed. For the identification of the parasites, permanent sheets were made using the clarification technique and the coloring technique. Monogenoid parasites found in the analysis were identified and described, and the parasite load was calculated. From the samples analyzed in Pterophyllum scalare, a monogenoid parasite species described in the literature as Gussevia spiralocirra was identified and recorded; while in the analysis of Biotodoma cupido, a monogenoid parasite of the genus Biotodomella and species Biotodomella mirospinata and a second species of monogenoid parasite of the genus Sciadicleithrum sp. Which is attributed as a new species. The parasite indices calculated for Pterophyllum scalare were higher, reaching 100% prevalence; while for Biotodoma cupido a maximum prevalence of 33.66% was reported. In this investigation it is concluded that Pterophyllum scalare has been parasitized by a single species of monogenoid known as Gussevia spiralocirra; y Biotodoma cupido has been parasitized by a monogenoid species described as a result of the results of this study, as well as a new species not yet described.